Sunday

November 23, 2014

November 23, 2014

Posted by **Anonymous** on Sunday, August 12, 2012 at 3:16pm.

Prove that tan^2(alpha)-1+cos^2(alpha)=tan^2(alpha)sin^2(alpha)

- Trigonometry -
**Steve**, Sunday, August 12, 2012 at 3:26pmsince cos(-x) = cos(x), what do you think?

cos(-x) = cos(0-x)

= cos0*cosx - sin0*sinx

= 1*cosx - 0

= cos(x)

**Answer this Question**

**Related Questions**

trig - express 20sin theta + 4 cos theta as R sin(theta + alpha) R sin(theta + ...

trig - FInd the exact value pf the 6 trig function of alpha Given: point (-2,-6...

Trigonometry - Prove that tan^2(alpha)-1+cos^2(alpha)sin^2(alpha) Please Explain

trig - evaluate the following in exact form, where the angeles alpha and beta ...

Math - Given that sin alpha=4/sqrt65, pi/2<alpha<pi, and cos beta=-3/...

Trigonometry - Find the counterexample to shows that the equation sec (alpha) - ...

maths (trigonometry) - sin(alpha-bita)=1/2 and cos(alpha+bita)=1/2, where alpha ...

physics - Two radar stations A and B, are separated by horizontal distance of (...

trig - in the diagram below.A,B and C are three points in the same horizontal ...

maths - prove that the length of the perpendicular from the origin to the ...